Formation of a high energy density field reversed configuration for compact toroid applications - Romadanov, I.V. (Вопросы атомной науки и техники, 2013)
Formation of a compact toroid (CT) or field reversed configuration (FRC) with a maximum input of energy and the capture of the magnetic field into plasma is an important scientific and technical challenge. The new method of CT formation is proposed and applications of CT/FRC are presented.